Pemeliharaan Anak Pasca Perceraian Pada Kasus Kekerasan Dalam Rumah Tangga Menurut Hukum Positif Indonesia - Fakhrurazi; Ananda, M. Rizqi; Sabili, Kholil Ahmad; Basyarahil, Ammar Muhzim; Al-Fikri, M. Abdu; Ray, M. Hapis; Rosfiani, Okta (Journal Evidence Of Law, 2024)
The aim of this research is to find out what positive legal views in Indonesia are regarding child maintenance rights after divorce due to domestic violence. This study conducted in order to know whether positive law in Indonesia regulates how children are cared for due to domestic violence, therefore the author looked for information related to this problem through books and also trusted journals, so that the information the author obtained could be used as information. A reference for learning how positive law in Indonesia regulates these problems. The research method that the author uses is qualitative (theoretical), where the author conducts research on books that discuss child care rights, and also on domestic violence, and the author also conducts research on journals and the internet, regarding these problems, and how positive law is applied. Indonesia regulates this problem. The results of this research explain that according to the compilation of Islamic law, Article 105 letter (a) regulates that the care of children who are not mumayyiz or who are not yet 12 years old is the right of the mother. Article 45 of Law Number 1 of 1974 states that parents are obliged to care for and educate their children as best as possible until the child marries or becomes independent, and this obligation will continue to apply. And based on law Number 23 of 2002 concerning Child Protection also states the rights and obligations of children, in this law child protection is given greater priority.